Genetic diversity and antibiotic resistance of Mycobacterium bovis in bovines in the Delta area of Egypt - Elsayed, Mohamed Sabry A.; Alqaim, Zahraa H.; Fayed, Aysam M.; Eldsouky, Samah Mahmoud; Basiouny, Mohamed Salah; Metwally, Azza M.; Abdelbadee, Ahmed; Hasan, Al Shaimaa; ElAlfy, Amira Kamal ElDin Mohammed; Nasr, Mai Afifi; Wahdan, Shimaa Mostafa Elnahas; Elsayed, Rasha Abdelhamid; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMycobacterium bovis (M. bovis) causes significant financial harm to the cattle industry through decreased productivity and trade limitations, while also posing a risk to human health through zoonotic transmission, which is primarily from unpasteurized milk or close animal contact.MethodsSingle intradermal tuberculin was used to test 2400 cases (1000 Holstein Friesian cattle and 1400 native breed buffaloes) during the national control program from Cairo, El-Buhaira, Dakahlia, Gharbia, Menoufia, and Sharkia districts located at the northern areas of Egypt. Tuberculin-positive cases were slaughtered and subjected to postmortem examination and isolation of M. bovis was performed. IS6110 primer was used in PCR test to confirm the existence of genus mycobacterium and regions of difference-based differentiation was used to detect M. bovis on the species level, phenotypic and genotypic antimicrobial resistance, as well as mycobacterial interspersed repetitive unit-variable number tandem repeat analysis (MIRU-VNTR) were performed.ResultsA total of 65 out of 2400 (2.7%) cases were single intradermal tuberculin test positive, 40 out of 65 (61.53%) were M. bovis positive on PCR, and the 40 isolates exhibited susceptibility to ethambutol, rifampicin, streptomycin, ciprofloxacin, levofloxacin, ofloxacin, and sparfloxacin. From them, 32 (80%) were susceptible to isoniazid, and 8 (20%) were resistant. These eight isolates contained three distinct katG mutations at codons 315, 463, and 506 with rates of 2/8 (25%), 3/8 (37.5%), and 3/8 (37.5%), respectively each representing a unique, single-codon mutation. MIRU-VNTR analysis enabled the identification of 35 distinct genotypes, with genotypes 26, 27, and 28 showing high prevalence. The nine highly discriminatory loci MIRU10, QUB11b, MIRU26, QUB26, QUB4156, MIRU04 ETRD, ETRA, Mtub30, and Mtub39 with a discriminating index of 0.9676 were suitable for the preliminary genotyping of M. bovis isolates from animals. M. bovis, ID: 7540/01, Lineage: Bovis and ID: 951/01, Lineage: Bovis from Germany were the closest lineages to our genotypes using the MIRU-VNTR plus database.ConclusionM. bovis isolated from cattle and buffaloes of some Delta area districts expressed high diversity and some isolates showed resistance to isoniazid with katG mutations. Continuous implementation of MIRU-VNTR analysis will help to trace the origin and similarities among animal and human isolates within the Delta area.